Helitrons in Drosophila: Chromatin modulation and tandem insertions. (3rd March 2016) - Dias, Guilherme B.; Heringer, Pedro; Kuhn, Gustavo C. S.
ABSTRACT: Although Helitrons were discovered 15 y ago, they still represent an elusive group of transposable elements (TEs). They are thought to transpose via a rolling-circle mechanism, but no transposition assay has yet been conducted. We have recently characterized a group of Helitrons in Drosophila, named DINE-TR1, that display interesting features, including pronounced enrichment at β-heterochromatin, multiple tandem insertions (TIs) of the entire TE, and that experienced at least 2 independent expansion events of its internal tandem repeats (TRs) in distant Drosophila lineages. Here we discuss 2 aspects of TE dynamics displayed by the DINE-TR1 Helitrons : (i) the general evolutionary impact of piRNA-guided heterochromatin formation via TE-derived TR expansion and (ii) the possible mechanisms that could account for the recurrent TIs of Helitrons .